Standard specification for Steel Bars, Carbon and Alloy, Hot-Wrought, General Requirements for (American Society for Testing and Materials, 2005)
This specifification2 covers a group of common requirements which, unless otherwise specifified in the purchase order or in an individual specifification, shall apply to carbon and alloy steel bars under each of the following ASTM specififications